Decompressive Craniectomy Is Associated With Good Quality of Life Up to 10 Years After Rehabilitation From Traumatic Brain Injury. Issue 8 (August 2020) - Rauen, Katrin; Reichelt, Lara; Probst, Philipp; Schäpers, Barbara; Müller, Friedemann; Jahn, Klaus; Plesnila, Nikolaus
Abstract : Objectives: Traumatic brain injury is the number one cause of death in children and young adults and has become increasingly prevalent in the elderly. Decompressive craniectomy prevents intracranial hypertension but does not clearly improve physical outcome 6 months after traumatic brain injury. However, it has not been analyzed if decompressive craniectomy affects traumatic brain injury patients' quality of life in the long term. Design: Therefore, we conducted a cross-sectional study assessing health-related quality of life in traumatic brain injury patients with or without decompressive craniectomy up to 10 years after injury. Setting: Former critical care patients. Patients: Chronic traumatic brain injury patients having not ( n = 37) or having received ( n = 98) decompressive craniectomy during the acute treatment. Measurements and Main Results: Decompressive craniectomy was necessary in all initial traumatic brain injury severity groups. Eight percent more decompressive craniectomy patients reported good health-related quality of life with a Quality of Life after Brain Injury total score greater than or equal to 60 compared with the no decompressive craniectomy patients up to 10 years after traumatic brain injury ( p = 0.004). Initially, mild classified traumatic brain injury patients had a median Quality of Life after Brain Injury total score of 83 (decompressive craniectomy) versus 62 (no decompressive craniectomy) ( p = 0.028). Health-related quality of life regarding physical status was better in decompressive craniectomy patients ( p = 0.025). Decompressive craniectomy showed a trend toward better health-related quality of life in the 61–85-year-old reflected by median Quality of Life after Brain Injury total scores of 62 (no decompressive craniectomy) versus 79 (decompressive craniectomy) ( p = 0.06). Conclusions: Our results suggest that decompressive craniectomy is associated with good health-related quality of life up to 10 years after traumatic brain injury. Thus, decompressive craniectomy may have an underestimated therapeutic potential after traumatic brain injury. Abstract : Supplemental Digital Content is available in the text.